Revitalisasi Landasan Pengembangan Kurikulum PAI Berbasis Al-Qur'an dan Hadis di Era Modern - Delli Marlina; Tia Aulia Redisti; Sumiarti Sumiarti (Najah Bestari, 2026)
The development of the modern era which is marked by technological advances and social changes requires adjustments in the development of the Islamic Religious Education (PAI) curriculum. This article aims to examine the revitalization of the foundation for developing the PAI curriculum based on the Al-Qur'an and Hadith so that it remains relevant to the needs of the times. This research uses a library research method with a descriptive qualitative approach through analysis of various literature related to the PAI curriculum and sources of Islamic teachings. The research results show that the values ​​of the Qur'an and Hadith must be included in the PAI curriculum through a contextual approach that is in line with advances in science and technology. The PAI curriculum must pay equal attention to cognitive and affective aspects, as well as psychomotor and affective aspects. In addition, the curriculum must be designed flexibly and adaptively while maintaining the basic principles of Islamic teachings. Therefore, it is hoped that the revitalization of the PAI curriculum will be able to produce students who are faithful, virtuous and have critical thinking skills that are relevant to today's demands.